Training university teachers in an urban context to educate future teachers in rural Mayan environments: an international cooperation project - Fernández-Larragueta, Susana; Martínez-Martínez, María José; Muñoz-López, Johana (Frontiers in Education, 2023)
This article is part of an International Cooperation Project funded by the Andalusian Agency for Development Cooperation of the Junta de Andalucía, Spain in collaboration with the Mayan Technological Institute (ITMES): 2018UC006 "Maestras y maestros para niñas y niños mayas en zonas rurales diseminadas: formando los formadores." (Teachers for Mayan girls and boys in remote rural areas: training the trainers). This cooperation project arose from the need of the university to develop a university degree program in teacher training in bilingual infant and primary education that would consider the characteristics of the communities these new professionals would impact: rural Mayan communities; is particularly interesting for three reasons: 1) the unit is attached to the University of San Carlos, the only public university in Guatemala, as a response to the Guatemalan Constitution that indicates the need for a Mayan University; 2) the unit's distinctive development for the formation and empowerment of Mayan culture; and 3) because its organizational structure combines receiving face-to-face instruction on weekends in the urban campus of San Juan de Chamelco-Cobán, the commercial and economic hub of the region, while during the week, students carry out their personal, professional and educational activities in rural areas.Thus, a double dimension: on the one hand, as will be developed further in this article, the selection and initial psycho-pedagogical-curricular training, attention to cultural, gender, and sociological diversity, of university teachers who, in the future, will be entrusted with the implementation and development of a university curriculum in teacher training aimed at and from the inclusion of children from Mayan rural communities. On the other hand, while considering the center's organizational structure, establishing the fundamental psycho-pedagogical and organizational principles with an inclusive curricular plan will allow the training of teachers whose actions will be carried out in rural Mayan environments. As a starting hypothesis, we consider that in order to provide quality, responsible and inclusive education to children from rural Mayan environments is necessary to approach this reality by linking vitally constructed knowledge and technical contents, so that they can be formulated and reformulated in a relevant way and thus generate powerful knowledge.